Unlocking Competitive Advantage: Key Moderating Factors for MSMEs Amidst the COVID-19 Era - Arum Wahyuni Purbohastuti; Yulia Nur Hasanah; Victor Prasetya; Sabil Sabil; Reza Rahmadi Hasibuan (Citakonsultindo, 2024)
COVID-19 hit Indonesian MSMEs worst (MSMEs). Only flexible MSMEs survived market upheavals. Customers want innovation. Market and entrepreneurial orientation effect SME competitiveness and marketing performance (SMEs). This study analyzes whether a competitive advantage could reduce the effects of market orientation and entrepreneurial orientation on pandemic firm performance. PLSE (PLS) (PLS). Statistics described responders. Gender, age, and education differ. Questionnaires found 104 MSMEs. Sector, location, length, starting capital, number of employees, monthly turnover, funding sources, and business ownership permits. EO and CA lower BP, while MO does not, the study found. MO promotes CA. CA doesn't affect MO and EO's BP.